Evaluation of the nephron‐sparing surgery formula in Wilms tumors. Issue 12 (18th August 2020) - Mrad, Chaima; Coulomb‐Lhermine, Aurore; Tabone, Marie‐Dominique; Ulinski, Tim; Audry, Georges; Irtan, Sabine
Abstract: Aim: Definitions of nephron‐sparing surgery (NSS) procedures in Wilms tumor (WT) are not clear. The new UMBRELLA protocol offers a formula (NSS(X)‐SRM( n )‐PRM( n )‐RRP( n %)) to better define the different NSS parameters. We aimed to assess the advantages and limits of this new formula. Methods: This retrospective monocentric study included patients operated by NSS for WT from 1975 to 2018. We reviewed the medical records and applied the NSS formula to all included patients. Results: Eighty kidneys were operated on 56 patients at a mean age of 19.2 months (4 days‐7.5 years), with 49 partial nephrectomies and 31 tumorectomies. The assessment of the surgical resection margins (SRM) showed a doubt in six cases and one tumor breach. An intact pseudocapsule along the resection margin with no renal parenchyma was found in four cases at pathological resection margins (PRM) assessment, whereas a tumor breach was described in seven cases. Among the six patients with a surgical doubt, only one had a pathological stage III. There were no surgical doubts in the seven patients with tumor breach at pathology. At a mean follow‐up of eight years (15 days‐28.6 years), eight patients had elevated blood pressure levels. Ten had proteinuria. These two parameters were significantly increased in patients with a remaining renal parenchyma (RRP) of less than half of the initial total renal parenchyma. The serum creatinine level was normal for all except two patients. Conclusion: The new NSS formula described all the crucial elements of NSS. RRP seemed essential for the evaluation of long‐term renal function.